2003
DOI: 10.1007/10929179_15
|View full text |Cite
|
Sign up to set email alerts
|

Socio-technical Perspectives on e-Government Initiatives

Abstract: Abstract. ICTs are intended to be a powerful tool in support of government transition to the "Digital Age". The purpose of this paper is to emphasize the importance of integrating a socio-technical perspective into the body of eGovernment practices. The current realisation in Italy of an "Action plan for eGovernment" is a source of interesting preliminary evidence for our purpose. Standard (Tool) Model vs. Socio-technical ModelIn a highly relevant paper Kling and Lamb [5] observe that most IS projects are typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…A sociotechnical system in an e-learning context is an information technology system that has an ongoing social process implementation, usually articulation work that is needed for IT activities. It considers the context of IT and the social use (Sorrentino and Virili, 2003). Therefore, we consider design-science research as the most suitable method for architectural design in this research.…”
Section: Methodsmentioning
confidence: 99%
“…A sociotechnical system in an e-learning context is an information technology system that has an ongoing social process implementation, usually articulation work that is needed for IT activities. It considers the context of IT and the social use (Sorrentino and Virili, 2003). Therefore, we consider design-science research as the most suitable method for architectural design in this research.…”
Section: Methodsmentioning
confidence: 99%
“…As Heeks concludes, both factors on technology and social approach along the evaluation process. In brief, a socio-technical approach is embedded in this model to emphasize the importance of human and social components of an information technology (Heeks, 2006b(Heeks, , 2006cKling & Lamb, 1999;Sorrentino & Virili, 2003). This plainly balances those two crucial factors in evaluating and assessing the gaps without concentrating merely on the technology and technical part in egovernment projects.…”
Section: Gapmentioning
confidence: 99%
“…A study by Irani et al (2002) concluded in analyses of criteria used in investment appraisals of local e-government in the UK that IS projects continue to give inadequate attention to human and social considerations. Further, Sorrentino and Virili (2003) conducted a systematic examination of the evaluation criteria specified in the Italian e-government Action Plan for assessing e-government project proposals to explore the underlying model of IS projects that was implicitly reflected in the plan. The investigators examined each of the five evaluation criteria against two models -(i) the model conceptualised by Kling and Lamb as the Standard (Tool) Model and (ii) a Socio-technical model.…”
Section: E-government As a Socio-technical Systemmentioning
confidence: 99%
“…The 'Standard Model' characterises the typical approach observed by Kling and Lamb in descriptions of IS development projects where ICTs are regarded principally as tools -albeit combined in complex configurations according to rule-based procedures and protocols. "Among other things, the Standard Model assumes that information systems are objective and rational, and thus capable of being evaluated through the use of objective tools and techniques" (Sorrentino and Virili, 2003). This approach equates to the technical approach to ICT design that Mumford describes (see Figure 1 above).…”
Section: E-government As a Socio-technical Systemmentioning
confidence: 99%
See 1 more Smart Citation